Gastronomy: an approach to studying food. Issue 4 (8th July 2014) - Maberly, Charlotte; Reid, Donald
Abstract : Purpose: – The purpose of this paper is to outline the curriculum of the UK's first MSc in Gastronomy. The programme supports an interdisciplinary approach to understanding food not yet commonly found in academia or beyond. However, it is increasingly recognized that such a perspective, as fostered by the MSc Gastronomy, may be key in effectively addressing complex contemporary problems within food culture and food systems. Design/methodology/approach: – This is a viewpoint paper that explains the rationale behind the chosen definition of Gastronomy, the context that inspired creation of the programme, an outline of the programme structure and justification of content. Findings: – The underpinning philosophy stems from a conviction that to address problems of corrupt food systems and problematic societal foodways, a more comprehensive understanding of food is needed. The programme seeks to cultivate this with a truly interdisciplinary approach to the study of food culture and food systems. This approach is recognized as an underrepresented area in academia where the study of food currently tends to be compartmentalized; a reductionist approach also mirrored within politics, commerce and our everyday lives. The MSc Gastronomy investigates how to foster and make commonplace, a more holistic and realistic understanding of food. Originality/value: – The MSc Gastronomy has been shaped by an understanding that a more comprehensive knowledge of food is required if contemporary problems within the food system are to be effectively addressed. To achieve this, the programme adopts an interdisciplinary approach to studying food only upheld by a small number of other academic institutions. It is the first of its kind in the UK, responding most closely to the specific cultural and political dynamics of Scotland's food culture.